Analysis Of Artificial Sweetener Content Of Sodium Cyclamate In Sugar Syrup Of Dawet Ice Sold At Pps Gresik Regency - Norainny Yunitasari; Nadya Ramadhanti; Anindi Lupita Nasyanka (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2026)
Many food and beverage sellers intentionally add hazardous chemicals to gain profits. For sweetening food or beverages, the chemical sodium cyclamate is sometimes added to reduce sugar consumption. Sodium cyclamate as an artificial sweetener will have a negative impact on health if consumed above the established threshold. One of the side effects of excessive consumption of sodium cyclamate is digestive disorders and kidney damage. This study aims to determine the presence of artificial sweeteners (sodium cyclamate) in the sugar syrup of dawet ice sold at the PPS Gresik Regency. The method used is a qualitative test, namely the precipitation method and the cyclamate test kit. There were three samples of dawet ice sugar syrup tested. The test results showed that the three samples tested did not contain sodium cyclamate. This is because there was no formation of white sediment in both test methods. Thus, the sugar syrup of dawet ice sold at the PPS Gresik Regency is declared safe from the use of sodium cyclamate.